Assessment of fibrosis and vascularization of bone marrow stroma of chronic myeloid Leukemia patients treated with imatinib mesylate and their relationship with the cytogenetic response (Brazilian Journal of Pharmaceutical Sciences, 2011)
Chronic Myeloid Leukemia (CML) is a myeloproliferative disease characterized by the presence of the Philadelphia chromosome (translocation between chromosomes 9 and 22), resulting in the formation of the hybrid BCR-ABL protein. Currently, the treatment of CML patients is performed with imatinib mesylate (IM), which promotes the elimination of leukemic cells by inhibiting the kinase activity of BCR-ABL. This study evaluated the effectiveness of IM by monitoring 22 CML patients in a chronic phase treated at the CEPON/SC with IM for a minimum follow-up period of two years. Cytogenetic Response (CR) and bone marrow biopsies (BMB) were evaluated before and after IM treatment. BMB were evaluated by detection of reticulin degree and vascularization. The results were correlated to the CR. Mean time to achieve CR was 9 months and was attained by 77.27% of the patients. The results from the initial BMB analysis showed that 59.09% presented reticulin of between 2+ and 4+ whereas after treatment, only 27.17% presented this degree. With regard to vascularization of the initial sample, 90.91% were graded between II and IV, whereas after treatment, 40.91% had this degree. The results suggest a positive correlation of degree of reticulin and vascularization with CR.